CHARACTERIZATION AND ACTIVATION OF NATURAL ZEOLIT FROM PONOROGO - Eddy Heraldy; Hisyam SW; Sulistiyono Sulistiyono (Indonesian Journal of Chemistry, 2003)
Characterization and activation of Natural Zeolite from Ponorogo (ZAP) have been done to improve the quality of zeolite as porous material. Analysis of mineral composition is done using X-Ray Difraction (XRD), Fourier Transform-Infra Red (FTIR) Spectroscopy and metal analysis using Atomic Absorption Spectroscopy (AAS). Characterization of the activated zeolite covered about number of acidic sites, surface area, ratio Si/Al and metal composition (Na, Ca, K and Fe). Activated processes is done using various mineral acid, i.e HCl, HNO3, H2SO4 and HPO4 with each concentration at 1 M and 3 3 hours dipping. The result showed that ZAP has composition Ca-klinoptilolit (43.09 %), gismondin (17.57 %), modernit (4.21 %) and quartz (10.37 %). The most efectif of the acid to activate is HCl and is proved to absorp of Zn in waste water. The effect of chemical activation is increasing the ratio of Si/Al, increasing the surface area and reducing some metal composition.